Modelling fully coupled mechanical, ecological, and hydrological feedback on peatland development - Mahdiyasa, Adilan (2024)
Mathematical models of peatland development have been employed to analyse peatland behaviour. However, the existing models of peatland development ignore the mechanical processes that potentially provide essential feedback on peatland ecology, hydrology, and resilience. This study aimed to develop a fully coupled mechanical, ecological, and hydrological model of peatland development, called MPeat, and examine the consequences of the feedback within the model. MPeat uses poroelasticity theory, which couples fluid flow and solid deformation to model the peat volume changes that lead to variations in peat physical properties, including bulk density, active porosity, and hydraulic conductivity. To validate poroelasticity formulation, the comparisons between numerical and analytical solutions of Terzaghi's and Mandel’s problems for one- and two-dimensional test cases are conducted. MPeat in one dimension that models peatland as a vertical column produces shallower water table depth and buffers the effect of climate changes on water balance, leading to greater quantities of carbon than the other peat growth models. Furthermore, by including the influence of vegetation on peat volume changes, MPeat exhibits the possibility of bistability, regime shifts, critical thresholds, and both short- and long-term peatland dynamical behaviour. The expansion of the model into two dimensions by incorporating horizontal space captures the spatial variation of peat thickness, water table depth, plant functional types, and peat physical properties. The comparison between one-dimensional and two-dimensional versions of MPeat illustrates that the lateral variability of peat physical properties helps peatland to accumulate more water and produces a higher carbon stock. The two-dimensional version of MPeat is employed to analyse the influence of river incisions at the edges and the limits to peatland carbon accumulation due to mechanical instability. River incision, together with the permeable substrate, reduces the water table position, which results in lower peat and carbon accumulation. Moreover, MPeat shows that peatland carbon accumulation in a landscape, consisting of upland, sloping area, and lowland, is limited by mechanical instability. Therefore, the results generated by MPeat highlight the possible importance of mechanical-ecohydrological feedback to the behaviour of peatland.